2023
DOI: 10.3390/ijms241210272
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and Elastic Emulsion Electrospun DegraPol Tubes Delivering IGF-1 for Tendon Rupture Repair

Abstract: Tendon injuries can result in two major drawbacks. Adhesions to the surrounding tissue may limit the range of motion, while fibrovascular scar formation can lead to poor biomechanical outcomes. Prosthetic devices may help to mitigate those problems. Emulsion electrospinning was used to develop a novel three-layer tube based on the polymer DegraPol (DP), with incorporated insulin-like growth factor-1 (IGF-1) in the middle layer. Scanning electron microscopy was utilized to assess the fiber diameter in IGF-1 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Pure DP electrospun tubes implanted around conventionally sutured rabbit Achilles tendons previously showed 20% decreased adherence of the newly formed tissue to neighboring areas 7 and we recently showed that addition of the insulin-like growth factor IGF-1 (DP-IGF-1) increased proliferation and matrix synthesis and increased mechanical superiority as compared to DP-only implants. 11 In order to further improve and decrease adhesion formation between implant and tissue, we developed two novel materials, using a blend of high molecular weight HA and PEO in a ratio of 1:1 and 1:4 (HA/PEO 1:1 and HA/ PEO 1:4, respectively), two commodity and cheap materials that are FDA approved and therefore easily translatable into the clinical setting. On the other hand, a further novel material based on pure DP treated with nAg (DP-Ag) was engineered to dampen bacterial attachment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pure DP electrospun tubes implanted around conventionally sutured rabbit Achilles tendons previously showed 20% decreased adherence of the newly formed tissue to neighboring areas 7 and we recently showed that addition of the insulin-like growth factor IGF-1 (DP-IGF-1) increased proliferation and matrix synthesis and increased mechanical superiority as compared to DP-only implants. 11 In order to further improve and decrease adhesion formation between implant and tissue, we developed two novel materials, using a blend of high molecular weight HA and PEO in a ratio of 1:1 and 1:4 (HA/PEO 1:1 and HA/ PEO 1:4, respectively), two commodity and cheap materials that are FDA approved and therefore easily translatable into the clinical setting. On the other hand, a further novel material based on pure DP treated with nAg (DP-Ag) was engineered to dampen bacterial attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Three materials are based on block-co-polymer DP, either pure (DP), 7 treated with silver nanoparticles (DP-Ag) or in combination with insulin-like growth factor 1 (DP-IFG-1). 11 Two materials are based on a blend of high-molecular-weight HA and PEO in a 1:1 (HA/ PEO 1:1) or 1:4 (HA/PEO 1:4) ratio, all serving the optimization of surgical tendon repair. All materials are planned to be implanted as thin, very elastic tubes around sutured tendons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations